IMPROVING STUDENTS READING COMPREHENSION BY USING MEDIA AT THE GRADE X3 OF SMA NEGERI I TAMBANG-KAMPAR - Kurniawan Kurniawan (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2015)
At the grade X3 of SMAN I Tambang, the researcher found that the students havelow reading comprehension. One of the factors was the students’ lack of vocabulary. Theaimed of this research was to identify whether media can better improve students’ readingcomprehension and to find out what factors can influence the improvement of students’reading comprehension at the tenth grade students of SMAN 1 Tambang. This research wasClassroom Action Research (CAR). It had been carried out since May to June 2011. It hadtwo cycles and consisted of four meetings in each cycles. The participants of this researchwere the students at class X3 of SMAN I Tambang. They consisted of 39 students. Theresearcher found that media can better improve students’ reading comprehension at the gradeX3 of SMA Negeri I Tambang-Kampar. In conclusion, media can help the students toimprove their reading comprehension. The finding of this research implies that the use ofmedia can be used to enhance the students’ reading comprehension in English reading class.